Failure of sexual reproduction found in micropropagated critically endangered plants prior to reintroduction: A cautionary tale - Ye, Q.; Bunn, E.; Dixon, Kingsley (2011)
Micropropagation is a useful technique for ex situ multiplication and restoration of critically endangered plant species, but the sexual reproductive behaviour of micropropagated plants is seldom evaluated prior to reintroduction. We examined the critically endangered species Rulingia sp. 'Trigwell Bridge', with only three remaining plants known in the wild, as a model case to examine this issue. Abnormalities in micropropagated plants of this species related to four floral traits (lengths of sepals, petals and anthers and width of anthers). The number of pollen grains per flower of abnormal individuals was lower than in plants with apparently normal flowers (wild types), but not significantly so (P=0.068). Pollen viability for the abnormal plant (0.87±0.26%) was significantly lower than for the plants exhibiting wild-type floral morphology (45.42±4.47%). Experimental manipulations were used to examine the mating behaviour of normal and abnormal plants. The results showed that both male and female reproductive failure was linked to individuals exhibiting abnormal flowering attributes. Such aberrant reproductive performance in a micropropagated rare species predicates caution when using micropropagated plants in reintroduction programmes, highlighting the importance of screening for reproductive normality prior to release of micropropagated plants (especially for critically endangered species where reliance on in vitro propagation methods is often a necessity).